2019
DOI: 10.1371/journal.pone.0210762
|View full text |Cite
|
Sign up to set email alerts
|

TULP3: A potential biomarker in colorectal cancer?

Abstract: Colorectal cancer (CRC) is the second most common cancer in women and the third most common cancer in men globally. The identification of differentially expressed genes associated to patient’s clinical data may represent a useful approach to find important genes in CRC carcinogenesis. Previously, the TULP3 transcription factor was identified as a possible prognostic biomarker in pancreatic ductal adenocarcinoma. Considering that pancreatic and colorectal tissues have the same embryonic origin, we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Besides, we unmasked that NEAT1 sponged miR-4688 to protect TULP3 from degradation. Importantly, TULP3 was reported as a prognostic marker in colorectal cancer and pancreatic ductal adenocarcinoma [33]. Additionally, we found that TULP3 elevation could reversed the effect of NEAT1 depletion on VSMCs development in AAA.…”
Section: Discussionsupporting
confidence: 50%
“…Besides, we unmasked that NEAT1 sponged miR-4688 to protect TULP3 from degradation. Importantly, TULP3 was reported as a prognostic marker in colorectal cancer and pancreatic ductal adenocarcinoma [33]. Additionally, we found that TULP3 elevation could reversed the effect of NEAT1 depletion on VSMCs development in AAA.…”
Section: Discussionsupporting
confidence: 50%
“…Dysregulation of TULPs has been implicated in a number of human diseases including retinitis pigmentosa (TULP1 and TULP2) ( 4 , 51 ), PKD (TULP3) ( 11 ), and several cancers (TULP3) ( 13 , 14 ). In fact, we queried the COSMIC (the Catalog of Somatic Mutations In Cancer) ( 52 ) database for mutations in TULP3 associated with cancer and identified with cancer and identified K320R, a mutation associated with endometrial carcinoma, which corresponds to a site of acetylation that we identified ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…TUB/TULPs carry out a diverse range of important physiological functions ranging from biotic and abiotic stress defense in plants to regulation of cell metabolism, intracellular transport, and neural differentiation in animals ( 8 ). Mutations in these genes have been associated with numerous conditions including impaired development ( 9 ), altered life span ( 10 ), kidney disease ( 11 , 12 ), and several cancers ( 13 , 14 ).…”
mentioning
confidence: 99%
“…An estimated 19.3 million new cancer cases and almost 10.0 million cancer deaths occurred in 2020 [ 1 ]. Messenger (m)RNA expressions play important roles in cancer cell progression and survival, and comparative gene expression profiles between tumors and adjacent tissues have been very useful in identifying potential cancer biomarkers [ 66 , 67 ]. Our results suggest that NSP3 (SH2D3C ) is differentially expressed in different cancer types and thus could serve different prognostic purposes in different cancer types.…”
Section: Discussionmentioning
confidence: 99%